Revealing The Educative and Musicality Values in Inculturation of Liturgical Music to Kristus Raja Semesta Alam Tegalrejo-Salatiga Catholic Church Community to Preserve The Existence of Traditional Music - Juanita Theresia Adimurti; Muhammad Jazuli; Agus Cahyono; Udi Utomo (International Conference on Science, Education, and Technology, 2021)
An inculturation has been made to liturgical music which aimed at supporting the creation of a more solemn worship atmosphere especially to help the people in their prayer as with singing, prayer can be expressed more deeply. The continuous use of traditional liturgical music can hold the value of education and musicality i.e. the traditional musical idioms for next generation. The liturgical music discussed in this article is from some regional tribe. Presenting the music, hopefully will reveal the educational values to the community, especially to those attending Kristus Raja Semesta Alam Tegalrejo-Salatiga Catholic Church. This research was conducted using qualitative description methods and case study approaches. Data were collected by doing field observations, interviews with users of some regional tribe liturgical music, and documentation. The results of the research shows the existence of the liturgical music educational values which lies in the beauty and resiliency of the idioms of some regional tribal music which are embedded and preserved in the involvement of religious worship. The aesthetic awareness of the music of some regional tribe on liturgical music emerged and became a social and cultural awareness of the church community of Kristus Raja Semesta Alam Tegalrejo-Salatiga. Thus the Liturgical Music of some regional tribe can be a mean to preserve the existence of traditional music in the community, especially in Catholic community.